Kemitraan Sekolah dengan Orang Tua dalam Meningkatkan Pembelajaran Partisipatif di TK Kusuma 1 Kab. Sleman - Fuaddiana, Amala Diska; Hibana, Hibana (STAI Auliaurrasyidin Tembilahan, 2024)
Parents’ involvement in kids’ education is significant for their development process and learning quality. Discontinuity between schools and parents in kid’s education will hinder their learning process. This study aims to determine the partnership built by Kusuma 1 Kindergarten, Sleman, Yogyakarta with parents in improving participatory learning. This research is qualitative. Data were collected using documentation and interviews with the school principal, teachers, and a representative of parents. The data were analyzed using an interactive analysis model developed by Miles and Huberman which includes data collection, data processing, data reduction, and conclusion drawing. The results showed that the school and parents made programmed activities, such as introducing the school’s vision, mission, and goals, parenting activities, learning activities outside the classroom with parents, P5 activities, and planning and evaluating the school budget for the learning process.